(untitled) (Medicine Today, 2026)
Introduction and objectives: Though laparotomy has been practiced for many years, the optimal procedure for repair of gut remains controversial. Gut suturing is an important part of gastrointestinal operations and can be achieved by hand suturing or by the newly developed staplers. The choice for suturing between a stapling device and a hand-sewn approach depends on the surgeon’s choice and experience of the surgeon. Technical fault of intestinal repair leads to leakage; regarded one of the most common complication in surgical practice & is more serious and life threatening condition. Recent advancement is the use of stapler as a device for gut repair. Because of the use of staplers technical failures is a rarity, suturing is more consistent. It can be used at difficult places. Aims: To assess and compare stapling and hand sewing method of anastomosis, the technique of stapling is better than hand sewing in a prospective study in patients undergoing elective gut surgery. Materials and Methods: The prospective comparative study was carried out in the Medical College for Women and Hospital (MCWH) and different private hospital, in Uttara, Dhaka, January 2019 to December 2023. A total of 100 cases which met the inclusion and exclusion criteria. The study population included patients who underwent elective gut surgeries for various conditions of stomach, small bowel, large bowel and rectum were alternatively placed in stapled and hand sewn group. One group A (n = 50) hand sewing and the other group B (n = 50) undergoing stapling. Outcome factors: anastomotic time, duration of operation, hospital stay. Results: The mean age was 41.82±12.31 and 45.48±11.96 yrs. in the hand-sewn group and stapled group respectively. Both mean and median ages were slightly higher in the stapler group (45.48 vs. 41.82 years; 45.5 vs. 42.5 years), but the differences were not statistically significant (p>0.05). The mean duration of surgery was 133.86±7.71 minutes in the stapled group and 146.50±5.28 minutes in the hand sewn group (P<0.05). Stapled group had significantly shorter anastomotic and operative times than hand sewn Group, with mean anastomotic times of 11.60 vs. 39.98 minutes and operative times of 133.86 vs. 146.50 minutes (p < 0.001). Post-operative complications were higher in the hand-sewn group, with lower rates of fever, infection, dehiscence, and leakage in the stapler group. Complication-free cases were more in the stapler group (80% vs. 42%). The overall difference was statistically significant (p=0.001). The stapler group had a significantly shorter hospital stay than the hand-sewn group (mean 8.94 vs. 11.78 days, p<0.001). Conclusion: With use of staplers there was a significantly decrease in duration of surgery. Stapling technique appears to be safer and accuracy as sutures. It reduced duration of hospital stay which helps ultimately in early return to routine work, importantly staplers can be used at places where hand sewn anastomosis is technically difficult. Stapler anastomosis is a new surgical innovation that can be performed successfully and safely. Medicine Today 2026, Vol.38 (1): 25-31